Pengembangan Kemampuan Manajemen Pemasaran Melalui Teknik Pengemasan dan Labeling Produk UMKM di Desa Kerato - Fendy Maradita; Anwar; Fahlia; Fadli Faturrahman; Rian Hardiansyah; Agus Santoso; Hartini; Jayanti Mandasari; Nurasia; Nurmaliyah (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this service is to expand product marketing and introduce product packaging to people in Kerato Village who have businesses. The method used is to provide counseling and training regarding product packaging techniques and product marketing. Marketing is the spearhead in a business, so this needs to be improved all the time and given knowledge about marketing that continues to grow. The result of this activity is that the community in Kerato village who have a business can better understand how to apply attractive packaging and carry out proper marketing so that they can increase their business.